2008
DOI: 10.1007/s11999-008-0552-5
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Small-magnitude Accelerations Enhance Bone Regeneration: A Preliminary Study

Abstract: High-frequency, low-magnitude accelerations can be anabolic and anticatabolic to bone. We tested the hypothesis that application of these mechanical signals can accelerate bone regeneration in scaffolded and nonscaffolded calvarial defects. The cranium of experimental rats (n = 8) in which the 5-mm bilateral defects either contained a collagen scaffold or were left empty received oscillatory accelerations (45 Hz, 0.4 g) for 20 minutes per day for 3 weeks. Compared with scaffolded defects in the untreated contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 49 publications
(72 reference statements)
3
23
0
Order By: Relevance
“…This is in accordance with literature findings on the protective effect of ALN not only in implant osseointegration, but also in bone regeneration settings such as fracture healing [40]. The anabolic effects of HF loading on bone and bone healing have been reported in several animal [16][17][18]42] and clinical trials [19,20]. It is well established that bone has the potential of sensing and responding to very small mechanical signals when applied at HF [43].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This is in accordance with literature findings on the protective effect of ALN not only in implant osseointegration, but also in bone regeneration settings such as fracture healing [40]. The anabolic effects of HF loading on bone and bone healing have been reported in several animal [16][17][18]42] and clinical trials [19,20]. It is well established that bone has the potential of sensing and responding to very small mechanical signals when applied at HF [43].…”
Section: Discussionsupporting
confidence: 90%
“…Previous in vivo studies have shown that well-controlled mechanical loading at low frequency can improve bone apposition onto the implant surface and bone formation and mineralization in the implant's vicinity [12][13][14][15]. The importance of using high-frequency (HF) mechanical loading, i.e., at a frequency beyond the physiological frequency (approx ∼3 Hz for mastication), is increasing because of the evidenced positive effect of HF loading on bone formation and fracture healing [16][17][18]. Furthermore, based on the clinical outcome of exercise studies [10,19,20], the advantages of using HF mechanical loading are considered to be safe and efficient.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies of Garman and colleagues (20) and Hwang and colleagues (21) showed that bone does not need to be loaded to be responsive to mechanical signals, and thus it may be that osteoblasts and their progenitors (mesenchymal stem cells) are sensitive to acceleration, thus facilitating application of the HFLMV signal. Our study supports these findings in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%